MEDIASI BETA SAHAM DALAM MODEL PERTUMBUHAN HARGA SAHAM DENGAN PROFITABILITAS DAN SUKU BUNGA - Deddy A. Suhardi (Media Riset Bisnis & Manajemen, 2009)
Understanding the empirical description of the behavior and role of beta is fundamental to portfolio risk management. This study evaluates the behavior of beta under the influence of stock prices' factors, and evaluates the role of beta affects the stock prices. Path analytical model was designed with beta as the intermediate variable where the interest rate factor and return on asset profitability factor were exogenous, and the average growth rate of stock prices movement became an endogenous variable.This model had been estimated by using the data of 32 property stocks listing at Indonesia Stock Exchange (BEI). Daily prices for the stocks, BEI Composite Index, profitabil4ty, and interest rate were obtained from BEI and Bank Indonesia tapes for January 2000 to December 2004 period.This analysis indicates that beta would become an effective intermediate variable for transmitting effect of the factors toward the stock prices. Stocks prices influence by beta which it influence by factors (interest rate and profitability), on the other hand, stocks prices influence by factors via beta. Here, if interest rate lead to set down or profitability grows up, of ceteris paribus, beta would forces up, and then the stocks prices would move up. The mediation of beta in this model has shown how the investors decide a stock be yet in their portfolio. The positive relationship of beta with stock prices show that investors like more sensitive stock on following market (higher beta). This decision forces most dominant by leading the economical setting (interest rate) rather than growing the firm's fundamental (ROA profitability). In this fact, the decision of investor is rational and indicated closely more interest minded.Keywords : Beta, Intermediate, Stock prices, Profitability, Interest rate